2012
DOI: 10.1021/om300551t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Perarylated 3,4-Disila-1,5-hexadienes. A Fluorescent Disilane Accommodated in the Crystal Lattice

Abstract: A dinickel complex with bridging silyl ligands, [{Ni(PCy3)}2(μ-SiHPh2)2] (1), prepared from [Ni(cod)2], PCy3, and H2SiPh2, underwent exchange of the PCy3 ligands with 1,2-bis(dimethylphosphino)ethane (dmpe) to yield a complex coordinated by the two bidentate ligands, [{Ni(dmpe)}2(μ-SiHPh2)2]. Reactions of diarylacetylenes, ArCCAr (Ar = C6H5, C6H4OMe-4, C6H4Me-4, C6H4F-4, C6H4CF3-4, C6H4CN-4), with 1 in a 4/1 ratio afforded 1,2-bis{(E)-1,2-diarylethenyl}-1,1,2,2-tetraphenyldisilanes via addition of the Si–H bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“… 39 At −60 C in C 7 D 8 , the SiH resonance is observed at 6.25 ppm with 1 J SiH = 167.9 Hz). , 40 4-47 was also prepared from 4-49 and 2 equiv of dmpe 41 29 Si was not observed due to decomposition of the complex during the measurement 42 4-50 was also prepared from Ni­(COD) 2 and Ph 2 SiH 2 in the presence of ( i Pr 3 P) …”
Section: Reactions Of Hydrosilanes With Transition Metal Complexesmentioning
confidence: 97%
See 3 more Smart Citations
“… 39 At −60 C in C 7 D 8 , the SiH resonance is observed at 6.25 ppm with 1 J SiH = 167.9 Hz). , 40 4-47 was also prepared from 4-49 and 2 equiv of dmpe 41 29 Si was not observed due to decomposition of the complex during the measurement 42 4-50 was also prepared from Ni­(COD) 2 and Ph 2 SiH 2 in the presence of ( i Pr 3 P) …”
Section: Reactions Of Hydrosilanes With Transition Metal Complexesmentioning
confidence: 97%
“…The products that have been obtained from the reactions of hydrosilanes with transition metal complexes are summarized in Tables (primary silanes), (secondary silanes), , ,, and (tertiary silanes)primarily for products that contain a Si–TM bond. Some researchers study reactions of primary and/or secondary and/or tertiary silanes.…”
Section: Reactions Of Hydrosilanes With Transition Metal Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, investigation of oligosilyl derivatives represents a significant challenge to understand the photophysical properties due to the effective σ–π conjugation through Si–Si bonds. Especially, diaryldisilanes are promising as soft crystals driven from the conformational variety and flexibility of Si–Si σ-bonds. Previously, we reported that the donor–acceptor disilane 1 (Figure ) displayed second harmonic generation (SHG) in the crystalline state, which is widely used in advanced photonic technologies. This compound has a strong transition dipolar moment by a strong donor moiety (−NMe 2 ) and an acceptor moiety (−CN) with Si–Si σ-conjugated linker, showing no absorption in the visible light region different from a large π-extended skeleton.…”
Section: Introductionmentioning
confidence: 99%